Hubungan Pengetahuan Ibu Terhadap Pemberian ASI Eksklusif Di Wilayah Kerja Puskesmas Batunyala - Nining Fatria Ningsih; Eli Arsanah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The purpose of this study was to determine the relationship between maternal knowledge about exclusive breastfeeding and the provision of exclusive breastfeeding in Puskesmas Batunyala, Lajut Village in 2024. Method: this research is the type of analytical correlation research with cross-sectional approach, data collection using a questionnaire with a total sampling technique, and data analysis using the Chi-Square test. Result: from 48 respondents, the results showed that most breastfeeding mothers were aged 20-35 years, 41 (85.42%), had a high school education, 24 (50%), were housewives, 45 (93.75%), were multiparous, 38 (79.17%), had a good level of knowledge, 31 (64.58%), most of them gave exclusive breastfeeding, namely 34 (70.83%), the Chi-Square Test obtained a p-value of 0.043 <0.05 indicating that there is a statistically significant relationship between maternal knowledge and exclusive breastfeeding.